Public's perceptions on procreation tax incentives. - Chong, Chee Yoon. (2008)
This report seeks to investigate the ability of Singapore's married tax resident, particularly the higher-income/educated group to perceive the regressive distribution of the tax savings from procreation tax incentives and its effectiveness in influencing their fertility behaviour were also examined.